Effectiveness of Flip Sheet and Poster Media on Knowledge and Attitudes related to Balanced Nutrition in Elementary School Children at SDN 009 Samarinda - Saydina Ananda; Satriani Amiruddin; Dini Indo Virawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
Nutritional problems in elementary school children are currently still quite high, both over-nutrition and under-nutrition. The prevalence of malnourished children in the world is around 14.3% with the number of children amounting to 95.2 million children. This type of research uses Quasy Experimental with pre-post-test with control group design. In this study there were 104 respondents. Knowledge and attitude data were obtained using a questionnaire. The results showed that there was a significant difference after education was carried out using flip sheets and posters in the experimental group and the control group. The significant knowledge result obtained was a p-value of 0.031 and the significant attitude value was obtained by a p-value of 0.009. By combining flipchart media with other teaching tools in this research, it is believed that it will contribute to further research and enable researchers to create research variables that are different from those currently used.